Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

The Scottish medicines in pregnancy programme: supporting the surveillance of medicines use during pregnancy and assessment of associated clinical outcomes - Tanja Mueller; Laura Stobo; Lynne Jarvis; Morven Millar; Emily Moore; Leanne Hopkins; Victoria Stark; Amy Hynd; Kwaku Osei-Oppong; Amanj Kurdi; Stuart McTaggart; Rachael Wood; et al. (European Journal of Clinical Pharmacology, 2026)

Pyridine degradation in autogenic supercritical water oxidation - Jianna Li; Conrad Austin; Stuart Moore; Nizette Consolazio; Shuzhong Wang; Igor V. Novosselov (Journal of Environmental Chemical Engineering, 2026)

Ammonia and organic carbon transformation in autogenic continuous flow supercritical water oxidation reactor - Jianna Li; Conrad Austin; Stuart Moore; Anmol Purohit; Shuzhong Wang; Jun Hu; Nizette Consolazio; John C. Kramlich; Igor V. Novosselov (Journal of Environmental Chemical Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

The many ages of Triton: New crater counts on the Voyager high-resolution image sequence and implications for impactor provenance - William B. McKinnon; Kelsi N. Singer; Stuart J. Robbins; Michelle R. Kirchoff; Simon B. Porter; Paul M. Schenk; Ted Stryk; Jeffrey M. Moore (Icarus, 2024)

Geology of the Utah Frontier Observatory for Research in Geothermal Energy (FORGE) Enhanced Geothermal System (EGS) Site - Clay Jones; Stuart Simmons; Joseph Moore (Geothermics, 2024)

Rock fishways: Natural designs for an engineered world - Ivor G. Stuart; Timothy J. Marsden; Matthew J. Jones; Matt T. Moore; Lee J. Baumgartner (Ecological Engineering, 2024)

Habitat structure shapes temperate reef assemblages across regional environmental gradients - Tim Jackson-Bué; Ally J. Evans; Peter J. Lawrence; Paul R. Brooks; Sophie L. Ward; Stuart R. Jenkins; Pippa J. Moore; Tasman P. Crowe; Simon P. Neill; Andrew J. Davies (Science of The Total Environment, 2024)

Destruction and defluorination of PFAS matrix in continuous-flow supercritical water oxidation reactor: Effect of operating temperature - Conrad Austin; Jianna Li; Stuart Moore; Anmol Purohit; Brian R. Pinkard; Igor V. Novosselov (Chemosphere, 2023)

Compactive deformation of incoming calcareous pelagic sediments, northern Hikurangi subduction margin, New Zealand: Implications for subduction processes - Maomao Wang; Philip M. Barnes; Julia K. Morgan; Rebecca E. Bell; Gregory F. Moore; Ming Wang; Ake Fagereng; Heather Savage; Davide Gamboa; Robert N. Harris; Stuart Henrys; Joshu Mountjoy; et al. (Earth and Planetary Science Letters, 2023)

PFOS destruction in a continuous supercritical water oxidation reactor - Jianna Li; Conrad Austin; Stuart Moore; Brian R. Pinkard; Igor V. Novosselov (Chemical Engineering Journal, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Climate change, disease range shifts, and the future of the Africa lion - Neil H. Carter; Paola Bouley; Sean Moore; Michael Poulos; Jérémy Bouyer; Stuart L. Pimm (Conservation Biology, 2018)
Article impact statement : Understanding causes and consequences of disease range shifts can help mitigate negative effects of such shifts on lions and other wildlife.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Weighting and indirect effects identify keystone species in food webs - Lei Zhao; Huayong Zhang; Eoin J. O'Gorman; Wang Tian; Athen Ma; John C. Moore; Stuart R. Borrett; Guy Woodward (Ecology Letters, 2016)
Species extinctions are accelerating globally, yet the mechanisms that maintain local biodiversity remain poorly understood. The extinction of species that feed on or are fed on by many others (i.e. ‘hubs’) has traditionally been thought to cause the greatest threat of further biodiversity loss. Very little attention has been paid to the strength of those feeding links (i.e. link weight) and the prevalence of indirect interactions. Here, we used a dynamical model based on empirical energy budget data to assess changes in ecosystem stability after simulating the loss of species according to various extinction scenarios. Link weight and/or indirect effects had stronger effects on food‐web stability than the simple removal of ‘hubs’, demonstrating that both quantitative fluxes and species dissipating their effects across many links should be of great concern in biodiversity conservation, and the potential for ‘hubs’ to act as keystone species may have been exaggerated to date.

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

Linking the green and brown worlds: the prevalence and effect of multichannel feeding in food webs - Elizabeth M. Wolkovich; Stefano Allesina; Kathryn L. Cottingham; John C. Moore; Stuart A. Sandin; Claire de Mazancourt (Ecology, 2014)
Recent advances in food‐web ecology highlight that most real food webs (1) represent an interplay between producer‐ and detritus‐based webs and (2) are governed by consumers which are rampant omnivores; feeding on varied prey across trophic levels and resource channels. A possible avenue to unify these advances comes from models demonstrating that predators feeding on distinctly different channels may stabilize food webs. Empirical studies suggest many consumers engage in such behavior by feeding on prey items from both living‐autotroph (green) and detritus‐based (brown) webs, what we term “multichannel feeding,” yet we know little about how common such feeding is across systems and trophic levels, or its effect on system stability. Considering 23 empirical webs, we find that multichannel feeding is equally common across terrestrial, freshwater, and marine systems, with >50% of consumers classified as multichannel consumers. Multichannel feeding occurred most often at the first consumer level, indicating that most taxa at the herbivore/detritivore level are more aptly described as multichannel consumers, and that such feeding is not restricted to predators. We next developed a simple four‐compartment nutrient cycling model for consumers eating both autotrophs and detritus with separate parameter sets to represent aquatic vs. terrestrial ecosystems. Modeling results showed that, across terrestrial and aquatic ecosystems, multichannel feeding is stabilizing at low attack rates on autotrophs or when attack rates are asymmetric (moderate on autotrophs while low on detritus), but destabilizing at high attack rates on autotrophs, compared to herbivory‐ or detritivory‐only models. The set of conditions with stable webs with multichannel consumers is narrower, however, for aquatic systems, suggesting that multichannel feeding may generally be more stabilizing in terrestrial systems. Together, our results demonstrate that multichannel feeding is common across ecosystems and may be a stabilizing force in real webs that have consumers with low or asymmetric attack rates.

Big claims for big weights but with little evidence - Nicholas A. Burd; Daniel R. Moore; Cameron J. Mitchell; Stuart M. Phillips (European Journal of Applied Physiology, 2013)

Similar increases in muscle size and strength in young men after training with maximal shortening or lengthening contractions when matched for total work - Daniel R. Moore; Mark Young; Stuart M. Phillips (European Journal of Applied Physiology, 2012)

Artificial gravity training reduces bed rest-induced cardiovascular deconditioning - Michael B. Stenger; Joyce M. Evans; Charles F. Knapp; Stuart M. C. Lee; Tiffany R. Phillips; Sondra A. Perez; Alan D. Moore; William H. Paloski; Steven H. Platts (European Journal of Applied Physiology, 2012)

Incorporating climate change adaptation into national conservation assessments - EDWARD T GAME; GEOFFREY LIPSETT‐MOORE; EARL SAXON; NATE PETERSON; STUART SHEPPARD (Global Change Biology, 2011)
The Convention on Biological Diversity requires that member nations establish protected area networks that are representative of the country's biodiversity. The identification of priority sites to achieve outstanding representation targets is typically accomplished through formal conservation assessments. However, representation in conservation assessments or gap analyses has largely been interpreted based on a static view of biodiversity. In a rapidly changing climate, the speed of changes in biodiversity distribution and abundance is causing us to rethink the viability of this approach. Here we describe three explicit strategies for climate change adaptation as part of national conservation assessments: conserving the geophysical stage, identifying and protecting climate refugia, and promoting cross‐environment connectivity. We demonstrate how these three approaches were integrated into a national terrestrial conservation assessment for Papua New Guinea, one of the most biodiverse countries on earth. Protected areas identified based on representing geophysical diversity were able to capture over 90% of the diversity in vegetation communities, suggesting they could help protect representative biodiversity regardless of changes in the distribution of species and communities. By including climate change refugia as part of the national conservation assessment, it was possible to substantially reduce the amount of environmental change expected to be experienced within protected areas, without increasing the overall cost of the protected area network. Explicitly considering environmental heterogeneity between adjacent areas resulted in protected area networks with over 40% more internal environmental connectivity. These three climate change adaptation strategies represent defensible ways to guide national conservation priority given the uncertainty that currently exists in our ability to predict climate changes and their impacts. Importantly, they are also consistent with data and expertise typically available during national conservation assessments, including in developing nations. This means that in the vast majority of countries, these strategies could be implemented immediately.

Nutrient provision increases signalling and protein synthesis in human skeletal muscle after repeated sprints - Vernon G. Coffey; Daniel R. Moore; Nicholas A. Burd; Tracy Rerecich; Trent Stellingwerff; Andrew P. Garnham; Stuart M. Phillips; John A. Hawley (European Journal of Applied Physiology, 2011)

Qualitative Variation in Proanthocyanidin Composition of Populus Species and Hybrids: Genetics is the Key - Ashley N. Scioneaux; Michael A. Schmidt; Melissa A. Moore; Richard L. Lindroth; Stuart C. Wooley; Ann E. Hagerman (Journal of Chemical Ecology, 2011)

COMPARATIVE ECOLOGY OF NORTH ATLANTIC SHORES: DO DIFFERENCES IN PLAYERS MATTER FOR PROCESS? - Stuart R. Jenkins; Pippa Moore; Michael T. Burrows; David J. Garbary; Stephen J. Hawkins; Agnar Ingólfsson; Kenneth P. Sebens; Paul V. R. Snelgrove; David S. Wethey; Sarah A. Woodin (Ecology, 2008)
The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large‐scale events, such as the trans‐Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and colonization. More recently, anthropogenically induced invasions and local extinctions have significantly altered biogeographic distributions. Here we consider for both hard and soft substrata how the presence or absence of key taxa influences the outcomes of trophic and other biological interactions, and evaluate the consequences for community structure and ecosystem functioning. On intertidal hard substratum shores, biodiversity of epilithic microphagous grazers differs across latitudinal and longitudinal scales. Diversity is high in southern Europe but declines to the north and across the Atlantic. Lower diversity and the absence of patellid limpets in Iceland and the northwest Atlantic compared to Europe result in differences in consumer pressure, and an apparent contrast in the importance of herbivory vs. competitive interactions and predation pressure as community structuring processes. Interestingly, despite differences in “process,” community patterns are remarkably similar between the east and west. On soft sediment shores, there are conspicuous geographic differences in importance of bioturbators and large digging predators. Hemichordates can be abundant and important infaunal bioturbators in the western Atlantic, but they generally play a much reduced role in the eastern Atlantic. In addition, the number and diversity of digging predators on western Atlantic shores is high; the horseshoe crab, swimming portunid crabs, large whelks, excavating waterfowl, and an abundance of skates and rays exert intense predation pressure and associated biogenic disturbance to sediments. In Europe, except for excavating waterfowl these taxa are rare or absent. Thus, the importance of large, biological agents of disturbance is lower on European shores as a consequence of both recent anthropogenic pressure and natural processes over larger time scales. Consideration of key structuring taxa over the Atlantic shows that human‐mediated transport has had considerable influence. Faunas on both sides of the Atlantic are becoming more similar to the point that some of the key differences in assemblage composition and hence community organization have blurred. Recent introductions as well as planned experimental manipulations provide the opportunity to understand the role of species identity in determining community structure and ecosystem functioning over large spatial scales; the North Atlantic may be an ideal test system to explore these areas.

Employment of 16S rDNA gene sequencing techniques for improved identification of difficult-to-identify bacterial veterinary pathogens - John E. Moore; Yasunori Maeda; Jiru Xu; B. Cherie Millar; Peter H. Herold; V. M. J. Browne-Lauwers; Colin E. Goldsmith; Anne Loughrey; Paul J. Rooney; J. Stuart Elborn; Motoo Matsuda (World Journal of Microbiology and Biotechnology, 2008)

The Brachyspira hyodysenteriae ftnA Gene: DNA Vaccinationand Real-Time PCR Quantification of Bacteria in a Mouse Modelof Disease - Antony J. Davis; Stuart C. Smith; Robert J. Moore (Current Microbiology, 2005)

Glucuronuria in the Koala - Stuart McLean; Sue Brandon; Noel W. Davies; Rebecca Boyle; William J. Foley; Ben Moore; Georgia J. Pass (Journal of Chemical Ecology, 2003)

Fate of the Dietary Terpene, P-Cymene, in the Male Koala - Rebecca Boyle; Stuart McLean; William J. Foley; Ben D. Moore; Noel W. Davies; Sue Brandon (Journal of Chemical Ecology, 2000)

Notes - H. C. Moore; N. J. Thomas; C. W. Metzger; E. R. Bennett; C. W. Hungerford; W M. Stuart; W M. H. Martin; E. B. Tussing; H. H. Zimmerley; H. O. Werner (American Journal of Potato Research, 1928)

Seed certification in british columbia - S. S. Phillips; E. A. Stokdyk; W. Stuart; H. C. Moore (American Journal of Potato Research, 1926)

Kiwanians sponsor potato club work - P. R. Young; E. V. Hardenburg; B. E. Brown; Paul M. Williams; Daniel Dean; A. G. Waller; H. R. Talmage; H. C. Moore; J. G. Milward; W. Stuart; H. B. Stevens; R. W. Goss; et al. (American Journal of Potato Research, 1925)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)

Potato notes - Lou D. Sweet; W. Stuart; E. V. Hardenburg; H. C. Moore; W. H. Martin (American Journal of Potato Research, 1923)